BK channels in microglia. Issue 1 (March 2023) - Sun, Xiaohui
Large-conductance calcium- and voltage-dependent potassium (BK) channels are ubiquitously expressed in mammalian cells and participate in various physiological and pathological processes such as neurotransmission and cerebral ischemia. BK channels comprise up to four pore-forming α subunits and zero to four accessory subunits. Although microglial BK currents were initially recorded 27 years ago, their roles have long been elusive. Studies have demonstrated that BK channels modulate the activation, phagocytosis, and probably migration of microglia and have associated microglial BK channels with many neurological diseases, including neuropathic pain and stroke. This review summarizes the available information regarding the biophysical, functional, and pathological aspects of microglial BK channels and discusses future directions of research into these channels.